SEN1990 is a predicted winged helix-turn-helix protein involved in the pathogenicity of Salmonella enterica serovar Enteritidis and the expression of the gene oafB in the SPI-17 - Hoppe-Elsholz, Guillermo; Piña-Iturbe, Alejandro; Vallejos, Omar P.; Suazo, Isidora D.; Sepúlveda-Alfaro, Javiera; Pereira-Sánchez, Patricia; Martínez-Balboa, Yohana; Catalán, Eduardo A.; Reyes, Pablo; Scaff, Valentina; Bassi, Franco; Campos-Gajardo, Sofia; et al. (Frontiers in Microbiology, 2023)
Excisable Genomic Islands (EGIs) are horizontally acquired genetic elements that harbor an array of genes with diverse functions. ROD21 is an EGI found integrated in the chromosome of Salmonella enterica serovar Enteritidis (Salmonella ser. Enteritidis). While this island is known to be involved in the capacity of Salmonella ser. Enteritidis to cross the epithelial barrier and colonize sterile organs, the role for most of ROD21 genes remains unknown, and thus identification of their function is fundamental to understand the impact of this EGI on the bacterium pathogenicity. Therefore, in this work we used a bioinformatical approach to evaluate the function of ROD21-encoded genes and delve into the characterization of SEN1990, a gene encoding a putative DNA-binding protein. We characterized the predicted structure of SEN1990, finding that this protein contains a three-stranded winged helix-turn-helix (wHTH) DNA-binding domain. Additionally, we identified homologs of SEN1990 among other members of the EARL EGIs. Furthermore, we deleted SEN1990 in Salmonella ser. Enteritidis, finding no differences in the replication/maintenance of the excised ROD21, contrary to what the previous Refseq annotation of the protein suggests. High-throughput RNA-sequencing was carried out to evaluate the effect of the absence of SEN1990 on the bacterium global transcription. We found a downregulated expression of oafB, an SPI-17-encoded acetyltransferase involved in O-antigen modification, which was restored when the deletion mutant was complemented ectopically. Additionally, we found that strains lacking SEN1990 had a reduced capacity to colonize sterile organs in mice. Our findings suggest that SEN1990 encodes a wHTH domain-containing protein that modulates the transcription of oafB from the SPI-17, implying a crosstalk between these pathogenicity islands and a possible new role of ROD21 in the pathogenesis of Salmonella ser. Enteritidis.